Early Evaluation of Provenance and Progeny Trial Combination of Araucaria Cunninghamii Age 12 Months in Bondowoso, East Java - Dedi Setiadi (Jurnal Ilmu Kehutanan)
A progeny test of Araucaria cunninghamii seedling seed orchard was established in 2008 in Bondowoso, East Java. The progeny trial comprises of eighty open-pollinated families collected from six seed sources (Fak-fak, Sorong, Serui, Wamena, Manokwari and Queensland). The trial was designed as a Randomized Complete Block Design (RCBD) consisted of 80 seedlots, 4 tree-line plots, 4 replicates with spacing of 4 m x 2 m. At 12 months of age there were significant differences  among provenances for tree height and stem diameter. The survival rate of all provenances was high (96.7 -100%). Differences between families within seed source were significant both for height and diameter growth. Estimated heritability for height was moderate (12f= 0.58; h2 = 0.28) and also for diameter (f = 0.55; h21 = 0.30). Genetic correlation between height and diameter was quite strong (rg = 0.78).